1988
DOI: 10.1002/eqe.4290160509
|View full text |Cite
|
Sign up to set email alerts
|

Non‐stationary spectral moments of base excited MDOF systems

Abstract: SUMMARYThe paper deals with the evaluation of non-stationary spectral moments of multi-degree-of-freedom (MDOF) linear systems subjected to seismic excitations. The spectral moments of the response are evaluated in incremental form solution by means of an unconditionally stable step-by-step procedure.As an application, the statistics of the largest peak of the response are also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…is consideration, which has originally been suggested by Borino et al [31], is not exactly correct when referring to the first time derivative of the envelope, as Shock and Vibration illustrated in Figures 5 and 6. In these two gures, it can be observed that some discrepancies exist between the approximate and exact nonstationary solutions, and they increase as the damping ratio diminishes.…”
Section: Numerical Resultsmentioning
confidence: 94%
“…is consideration, which has originally been suggested by Borino et al [31], is not exactly correct when referring to the first time derivative of the envelope, as Shock and Vibration illustrated in Figures 5 and 6. In these two gures, it can be observed that some discrepancies exist between the approximate and exact nonstationary solutions, and they increase as the damping ratio diminishes.…”
Section: Numerical Resultsmentioning
confidence: 94%
“…In many cases of engineering interest the probabilistic assessment of structural failure is derived as a function of barrier crossing rates, distribution of peaks and extreme values. These quantities can be evaluated as a function of the so-called Non-Geometric Spectral Moments (NGSMs) [12,13,14] for non-stationary stochastic processes.…”
Section: Explicit Solutions For the Ngsmsmentioning
confidence: 99%
“…Unfortunately, the solution of this problem has not been derived in exact form, even in the simplest case of the stationary response of a Single-Degree-of-Freedom (SDoF) linear oscillator under zero mean Gaussian white noise. In the framework of approximate methods, for zero-mean Gaussian non-stationary input, the evaluation of the so-called Non-Geometric Spectral Moments (NGSMs) is required [12][13][14][15][16]. Therefore the j-th NGSMs, , () ii uu t , is a complex quantity whose real part can be evaluated as the cross-covariance between the response process and the response velocity process of the same linear system subjected to a non-stationary input whose stationary counterpart is proportional to its Hilbert transform.…”
Section: Explicit Solutions For the Ngsmsmentioning
confidence: 99%
“…The amplitude non-stationarity has been tackled in studying the response of single-degree-of-freedom (SDOF) and MDOF systems mostly by modelling the input as a uniformly modulated stationary process. Some of the popular amplitude modulating functions, also referred to in the literature as 'strength function', used for this purpose include step function by Caughey and Stumpf, 1 6 exponentially decaying function by Corotis and Marshall, 7 To, 8 and Borino et al, 9 and piecewise linear functions by Gasparini and DebChaudhury. 10 Several other researchers, e.g.…”
Section: Introductionmentioning
confidence: 99%